2019
DOI: 10.1186/s10033-019-0318-x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the Influence of Tool Runout on Surface Generation in Micro Milling

Abstract: Micro milling is a flexible and economical method to fabricate micro components with three-dimensional geometry features over a wide range of engineering materials. But the surface roughness and micro topography always limit the performance of the machined micro components. This paper presents a surface generation simulation in micro end milling considering both axial and radial tool runout. Firstly, a surface generation model is established based on the geometry of micro milling cutter. Secondly, the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The significance of tool runout is that it has a major influence on the cutting force. This is due to the displacement being in the same order of magnitude as the feed per tooth, which therefore has a large influence on the surface roughness generated, as determined recently by Chen et al [ 99 ]. They also found that axial runout in particular limited the achievable surface roughness.…”
Section: Fundamentals Of the Processmentioning
confidence: 83%
See 1 more Smart Citation
“…The significance of tool runout is that it has a major influence on the cutting force. This is due to the displacement being in the same order of magnitude as the feed per tooth, which therefore has a large influence on the surface roughness generated, as determined recently by Chen et al [ 99 ]. They also found that axial runout in particular limited the achievable surface roughness.…”
Section: Fundamentals Of the Processmentioning
confidence: 83%
“…Therefore, axial displacement of the tool causes its tip to rotate off center relative to the spindle axis. Cutting tools will generally be less tolerant to axial runout, especially for micro-milling operations in both side and face milling operations, but axial runout has a considerable influence on the surface topography generation in face milling [ 99 ]. The total tool runout is therefore the sum of both axial and radial runouts, with the effect becoming even more significant in the micro-milling domain, as demonstrated by Fig.…”
Section: Fundamentals Of the Processmentioning
confidence: 99%
“…This model has the advantages of a simple form, relatively easy calculation, and high reliability. Chen et al [15][16][17] established a vaporization phase transition calculation model based on the viscosity-temperature effect. The saturation temperature with the pressure change equation, fluid internal friction effect, and the phase transition mechanism of the spiral groove liquid film seal were analyzed and discussed.…”
Section: Introductionmentioning
confidence: 99%